A study of the histopathological spectrum of thyroid neoplasms in a tertiary health care center - Rabia Parveen Siddiqui; Vanita Bhaskar; Kavita Swami; Varsha Pandey; Anubhav Chandrakar; Kasturi Mangrulkar (MGM Journal of Medical Sciences)
Background: Thyroid gland lesions are common and can result from systemic conditions such as Graves’ disease or localized abnormalities like nodular enlargement or tumors. Thyroid malignancies are the most prevalent endocrine cancers, accounting for approximately 92% of all endocrine malignancies. This study aims to explore the spectrum of thyroid neoplasms in a tertiary healthcare center. Aims and Objectives: The primary objective of this study was to examine the histopathological spectrum of thyroid neoplasms in a tertiary healthcare center. Additionally, the study aims to assess the frequency of various thyroid neoplasms across different age groups and genders and to identify any associated nonneoplastic thyroid lesions that occur alongside thyroid neoplasms. Materials and Methods: This observational descriptive cross-sectional study was conducted in the Department of Pathology, Pt. Jawahar Lal Nehru Memorial Medical College, Raipur, Chhattisgarh, India, over 50 months from January 2020 to March 2024. A total of 71 cases meeting the inclusion criteria were analyzed. Results: Of the 71 thyroid specimens examined, 12 cases (16.9%) were benign, whereas 59 cases (83.09%) were malignant. The study demonstrated a significant female predominance with a female-to-male ratio of 9.1:1 (64 females and 7 males). Most cases were observed in the 21–30 years age group, with a mean age of 32.3 years. Papillary carcinoma was identified as the most common malignant lesion, accounting for 35 cases (52.1%), whereas follicular adenoma was the most common benign lesion, accounting for 9 cases (12.7%). Conclusion: Accurate diagnosis of thyroid malignancies requires a combination of clinical history, radiological imaging, thyroid function tests, and thorough histopathological examination. Early and proper diagnosis facilitates more effective treatment decisions, standardized management protocols, and improved patient outcomes.